The Influence of Online Consumer Reviews, Prices, and Consumer Trust on Online Purchase Decisions for Skincare Products on Shopee - Kristin, Julie; Widiyanti, Marlina; Saggaff Shihab, Muchsin; Rosa, Aslamia (International Journal Labs, 2024)
In the digital era, consumer purchasing decisions are increasingly influenced by various online factors, especially on e-commerce platforms such as Shopee. For skincare products, consumer reviews, price, and consumer trust levels are key factors that influence purchasing decisions. With more product choices and information available, it is important to understand how these factors influence consumer decisions. This study aims to examine the influence of online consumer reviews, price, and consumer trust on online purchasing decisions for skincare products on Shopee, given the importance of these factors in purchasing decisions in a competitive e-commerce market. This study aims to determine the effect of online consumer reviews, price, and consumer confidence on online purchasing decisions for skincare products at Shopee. The type of data used in this study is primary data obtained by distributing questionnaires. Respondents in this study were Shopee users who purchased skincare products in the period January - April 2024 with a sample size of 95 respondents. The data analysis technique used in this research is Multiple Linear Regression with the absolute value difference test method using SPSS 29.0. The results of this study prove that online consumer reviews, prices, and consumer confidence have a positive influence on online purchasing decisions for skincare products at Shopee. The results of this study imply that consumer reviews, price, and consumer trust are crucial factors that sellers of skincare products on Shopee must pay attention to in order to influence purchasing decisions. Sellers are advised to actively manage and respond to consumer reviews to build trust and improve their product reputation.